IMPELEMENTASI SISTEM INFORMASI MANAJEMEN DAN KONTRIBUSINYA TERHADAP PEMASARAN JASA PENDIDIKAN - musradinur Musradinur (Program Studi Administrasi Bisnis, 2023)
Every educational institution is currently trying to implement information technology in order to increase effectiveness and efficiency in the information service process, this aims to provide added value which is a competitive advantage and also in an effort to meet the needs and desires of users by continuously making improvements. Implementation of the Education Management Information System as a method that can produce precise and fast information for management about the external and internal environment which is expected to provide quality services. The implementation of management information systems makes a major contribution to the marketing of educational services in the era of globalization, where every educational institution competes to provide the best offers. For educational institutions that sell services or products using technological networks with the aim of improving the quality of educational institutions.